Nephroprotective Power of Allium ampeloprasum Subsp. Iranicum: Attenuating Cyclophosphamide-Induced Kidney Injury through Antioxidant and Anti-Inflammatory Mechanisms: Allium ampeloprasum Subsp. Iranicum: Natural Shield Against Toxicity - Abedi, Fatemeh; Yousefsani, Bahareh Sadat; Shirani, Kobra (Iranian Journal of Pharmaceutical Sciences, 2026)
The kidneys are essential organs that perform key functions for maintaining homeostasis. Cyclophosphamide (CP), a widely used chemotherapy agent, can cause nephrotoxicity through multiple mechanisms driven by oxidative stress. Allium ampeloprasum subsp. Iranicum, known for its antioxidant and anti-inflammatory properties, contains bioactive compounds that may mitigate these adverse effects. The study aims to determine whether the antioxidant properties of A. ampeloprasum can help maintain kidney function and enhance the effectiveness of treatment during CP therapy. Mice were divided into four groups: negative control, A. ampeloprasum only (150 mg/kg), CP-treated (20 mg/kg), and combined A. ampeloprasum (150 mg/kg) with CP (20 mg/kg). Treatments were administered both orally and intraperitoneally over 14 days. Blood and tissue samples were analyzed for biochemical, histopathological, and molecular markers, including lipid peroxidation, antioxidant enzymes, and inflammatory cytokines. The data were analyzed using one-way analysis of variance (ANOVA) followed by Tukey's post-hoc test for multiple comparisons. CP treatment resulted in significant weight loss, tissue inflammation, and structural kidney damage, along with elevated serum markers of kidney injury, increased lipid peroxidation, and decreased antioxidant enzyme activities. Histopathological analysis confirmed inflammatory changes and tissue disruption caused by CP, which were significantly mitigated by pretreatment with A. ampeloprasum extract. This extract reduced serum levels of urea, creatinine, and uric acid, and decreased lipid peroxidation in tissues. It boosted antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px). Additionally, A. ampeloprasum pretreatment markedly reduced levels of inflammatory cytokines compared with CP alone. This study demonstrates that A. ampeloprasum extract effectively mitigates CP-induced toxicity by reducing oxidative stress, inflammation, and tissue damage, indicating its potential as a natural protective agent during chemotherapy.